Gender, crime and terrorism: the case of Arab/Palestinian women in Israel - Berḳo, ʿAnat (The British journal of criminology, 2010)
This article compares the background, motivation, pathways and prison experiences of Arab/Palestinian women who were imprisoned for conventional crimes with those who were incarcerated for security-related or terrorism offences. In-depth interviews of the two groups were conducted in the Israeli prisons in which they served their sentences. Prison personnel were also interviewed and court and prison files examined to validate the women's background and criminal history. Although both groups transgressed gender expectations by venturing into male-dominated worlds (crime and terrorism), the data point to differences between the groups regarding their personal background and the manner in which their violations were influenced by gender and the Israeli-Palestinian conflict. The implications of the findings for differences between crime and terrorism as related to gender and Palestinian terrorism are discussed